2011
DOI: 10.1111/j.1654-1103.2011.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Silver fir stand productivity is enhanced when mixed with Norway spruce: evidence based on large-scale inventory data and a generic modelling approach

Abstract: Questions: How to evaluate the mixture effect on basal area increment in two‐species forest stands? Is a mixed Norway spruce–silver fir stand more productive than pure adjacent stands of either species? How to develop generic modelling approaches to assess mixture effects in forest stands? Location: In addition to a case study on Norway spruce–silver fir stands in French mountain forests, the generic approach used goes beyond local applications. Methods: We took advantage of National Forest Inventory data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 32 publications
3
42
1
Order By: Relevance
“…This result supports the hypothesis that complementarity of light use could be at the origin of the over-yielding that has been observed in some mixed stands (Toïgo et al, 2015;Pretzsch and Schütze, 2009;Vallet and Pérot, 2011). The difference between the observed values of transmittance in mixed stands and weighted averages originates, at least partly, from the non-linearity of the relationship between light transmittance and stand basal area (Comeau and Heineman, 2003;Lochhead and Comeau, 2012;Sonohat et al, 2004).…”
Section: Tree Light Capture and Overstory Heterogeneitysupporting
confidence: 76%
See 2 more Smart Citations
“…This result supports the hypothesis that complementarity of light use could be at the origin of the over-yielding that has been observed in some mixed stands (Toïgo et al, 2015;Pretzsch and Schütze, 2009;Vallet and Pérot, 2011). The difference between the observed values of transmittance in mixed stands and weighted averages originates, at least partly, from the non-linearity of the relationship between light transmittance and stand basal area (Comeau and Heineman, 2003;Lochhead and Comeau, 2012;Sonohat et al, 2004).…”
Section: Tree Light Capture and Overstory Heterogeneitysupporting
confidence: 76%
“…It has been advocated that forests with many tree species and a great heterogeneity in tree sizes are more productive (Pretzsch and Schütze, 2009;Vallet and Pérot, 2011;Toïgo et al, 2015), resistant and resilient (Jactel et al, 2005) to future changes and harbor a greater biodiversity (Huston, 1979) than monospecific forests in which all trees have a similar size. Over the last 50 to 100 years, humans have applied forest management systems over much of the northern hemisphere that tended to simplify both the structure and composition of many forests (Bengtsson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies based on forest inventory plots (Condés et al 2013;Vallet and Pérot 2011) may cover a certain portion of fully stocked pure and mixed-species stands. However, if the stand history is unknown, it remains open as to which plots are really at maximum stand density.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Recent empirical studies of mixed forest long-term experiments (Bielak et al 2014;Pretzsch et al 2010Pretzsch et al , 2013a, studies using large-scale data bases (del Río and Sterba 2009;Río et al 2014a;Vallet and Perot 2011), simulation model studies (Morin et al 2011), as well as meta-analyses (Griess and Knoke 2011;Paquette and Messier 2011;Piotto 2008;Zhang et al 2012), showed that the productivity of mixed stands can exceed the weighted mean productivity of pure stands. This overyielding can reach 50 % in mixture with nitrogen-fixing species (Forrester et al 2006) and 20-30 % in other mixtures (Pretzsch et al 2013a).…”
Section: Introductionmentioning
confidence: 99%